Update on the Pathogenesis, Clinical Diagnosis, and Treatment of Hirayama Disease - Wang, Hongwei; Tian, Ye; Wu, Jianwei; Luo, Sushan; Zheng, Chaojun; Sun, Chi; Nie, Cong; Xia, Xinlei; Ma, Xiaosheng; Lyu, Feizhou; Jiang, Jianyuan; Wang, Hongli (Frontiers in Neurology, 2022)
Hirayama disease (HD) is characterized by the juvenile onset of unilateral or asymmetric weakness and amyotrophy of the hand and ulnar forearm and is most common in males in Asia. A perception of compliance with previous standards of diagnosis and treatment appears to be challenged, so the review is to update on HD. First, based on existing theory, the factors related to HD includes, (1) cervical cord compression during cervical flexion, (2) immunological factors, and(3) other musculoskeletal dynamic factors. Then, we review the clinical manifestations: typically, (1)distal weakness and wasting in one or both upper extremities, (2)insidious onset and initial progression for 3–5 years, (3)coarse tremors in the fingers, (4)cold paralysis, and(5)absence of objective sensory loss; and atypically, (1)positive pyramidal signs, (2)atrophy of the muscles of the proximal upper extremity, (3) long progression, and(4) sensory deficits. Next, updated manifestations of imaging are reviewed, (1)asymmetric spinal cord flattening, and localized lower cervical spinal cord atrophy, (2)loss of attachment between the posterior dural sac and the subjacent lamina, (3)forward displacement of the posterior wall of the cervical dural sac, (4) intramedullary high signal intensity in the anterior horn cells on T2-weighted imaging, and(5) straight alignment or kyphosis of cervical spine. Thus, the main manifestations of eletrophysiological examinations in HD include segmental neurogenic damages of anterior horn cells or anterior roots of the spinal nerve located in the lower cervical spinal cord, without disorder of the sensory nerves. In addition, definite HD needs 3-dimensional diagnostic framework above, while probable HD needs to exclude other diseases via “clinical manifestations” and “electrophysiological examinations”. Finally, the main purpose of treatment is to avoid neck flexion. Cervical collar is the first-line treatment for HD, while several surgical methods are available and have achieved satisfactory results. This review aimed to improve the awareness of HD in clinicians to enable early diagnosis and treatment, which will enable patients to achieve a better prognosis.